Gold nanoparticles functionalized with 4,4’-dithiobiphenyl blended with CuS in PMMA for switching memory devices - Cerra, Sara; Pica, Paride; Congiu, Mirko [UNESP]; Boratto, M. H. [UNESP]; Graeff, C. F.O. [UNESP]; Fratoddi, Ilaria (My University, 2020)
A switching memory device based on functionalized gold nanoparticles (AuNPs) and hexagonal copper sulfide nanocrystals (CuS), finely blended in polymethylmethacrylate matrix (PMMA), is herein presented. A two-electrode sandwich architecture has been implemented using aluminum top and bottom electrodes and a polymeric insulating layer based on PMMA/AuNPs/CuS. The device showed memory storage capabilities suitable for (Read Only Memory) ROM applications and behaves as a typical Write-Once, Read-Many-times (WORM) device. The results obtained with the blend containing AuNPs and/or CuS were compared with pure PMMA. By a voltage ramp in the range ± 9 V, it was possible to permanently change the electrical resistance between the electrodes yielding an ON/OFF current ratio above 105 with long-term stability over the whole experiment duration (30 days).